Analysis Of Joint Cost Calculation In Determining Cost Of Production Cv. Alfar Bakery - Rahmawati, Siti Shasinta; Cahyana, Agus; Azis, Azolla Degita; Asvariwangi, Verni (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2022)
The purpose of writing this thesis is to determine the calculation and knows the amount of profit/loss earned by the company. In this study using the relative selling value method, the authors conclude that: in calculating the allocation of joint costs at CV. Alfar Bakery generates a total cost of Rp 44.132.130. That it can be estimated that the total joint cost generated are 10% to the CV. Alfar Bakery revenue results. So that this company can determine the selling price of its products precisely and accurately, in the sense that it is neither too low nor too high.